Seasonal Responses of Hydraulic Function and Carbon Dynamics in Spruce Seedlings to Continuous Drought - Han, Yangang; Deng, Jiaojiao; Zhou, Wangming; Wang, Qing-Wei; Yu, Dapao (Frontiers in Plant Science, 2022)
Drought is expected to increase in the frequency and duration associated with climate change. Although hydraulic function and carbon (C) storage have been widely recognized as key components to plant survival under single drought, the physiological responses to continuous drought remain largely unknown, particularly for high northern temperate and boreal forests which are sensitive to water stress. In the present study, we quantified the survival, growth, gas exchange, water relations, and non-structural carbohydrates (NSC) in three-year-old Jezo spruce (Picea jezoensis) seedlings responding to continuous drought stress. Seedlings were maintained in drought conditions for 392 days, covering two growing and one dormant winter seasons. Seedlings subjected to drought showed significant decrease in net photosynthesis rate (Anet) and stomatal conductance (gs) in both growing seasons, and biomass in the second growing season. The seedling mortality continuously increased to 35.6% at the experimental end. Notably, responses of C storage and leaf water potential to drought varied greatly depending on seasons. Living seedlings exposed to drought and control treatments had similar NSC concentrations in both growing seasons. However, seedlings with concentrations of both the soluble sugars and starch less than 1 % in root died in the winter dormant season. In the second growing season, compared with control treatment, droughted seedlings had significantly lower leaf water potential and stem wood-specific hydraulic conductivity (Kw). Meanwhile, the leaf predawn water potential didn’t recover overnight. These suggest that C starvation might be an important reason for seedlings that died in the winter dormant season, while in the growing season drought may limit seedling survival and growth through inducing hydraulic failure. Such seasonal dependence in hydraulic dysfunction and C depletion may lead to higher mortality in spruce forests facing extended drought duration expected in the future.